PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA SD/MI - Syafitria, Adesta; Dwi Ariesta, Adinda; Berlianna, Romsiah; Fatimah, Siti; Putri, Trianita Melya (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
One thing that needs to be prepared by the teacher to support the delivery of learning material and the success of an education is audio-visual learning media. The purpose of this study was to determine the application of audio- visual media in learning activities, the advantages and benefits of audio-visual media in increasing student learning interest and student enthusiasm in teaching and learning activities in class. This study uses a qualitative method that is used in this study is a qualitative approach in the nature of literature study, the technique used is literature review and the data sources to be obtained later come from Mendeley and Google Scholar. Data collection techniques are used to compare data with different numbers, research data obtained from journal and literature analysis. The results of this study are that the use of audio visual media in the teaching and learning process can make learning interesting and not boring, so that this media is highly recommended by teachers in the learning process, and students are more interested in listening and paying attention to the material being taught. by the teacher. Therefore, the use of audio-visual media is very effective in capturing content or subject matter because it can generate motivation and interest in learning among SD/MI students.